Analysis of rrs gene mutations in amikacin resistant clinical isolates of Mycobacterium tuberculosis from Khyber Pakhtunkhwa, Pakistan. (July 2017) - Ahmad, Kafeel; Ahmad, Zeeshan; Somayya, Ramla; Ali, Amjad; Rahat, Shaista
Abstract: Tuberculosis is a major infectious disease caused by Mycobacterium tuberculosis complex. Antimicrobial drugs are used to control TB infections. Molecular mechanisms controlling resistance to second-line drugs are not completely understood and no endogenous information is available regarding these mechanisms. The present study reports mutational analysis of rrs gene in Mycobacterium tuberculosis isolates collected from Khyber Pakhtunkhwa province of Pakistan. A total of 499 Mycobacterium tuberculosis isolates were analyzed for resistance against amikacin. Thirty resistant isolates were selected for mutational analysis in rrs gene. Among the 30 amikacin resistant isolates of Mycobacterium tuberculosis, 9 (30%) had mutation in the hotspot region of rrs gene. The predominant mutation was 1401A > G which was observed in 5 isolates. Maximum number of mutations was observed in isolate 6 and isolate 16 with six different mutations each. Mutations in isolate 6 included 1260G > A, 1278A > T, 1278_1279insT, 1300C > T, 1321G > A and 1445C > T. Mutation in isolate 16 included 1255_1256insA, 1364_1365insG, 1384_1385insA, 1880_1881insT, 1487G > A, and 1493delA. The mutation 1263G > A was observed in isolate 1. Isolate 2 had the 1484G > T mutation. The findings could be used as reference for future endures. It was evident from the results that mutations in rrs gene do not always contribute to amikacin resistance; hence, traditional drug susceptibility testing is still helpful for evaluation of such samples. Highlights: A number of different mutations in the hot spot region of rrs gene were observed among Mycobacterium tuberculosis isolates. The predominant mutation was 1401A > G. The findings could be used as reference for future endures. It was evident from the results that mutations in rrs gene do not always contribute to amikacin resistance; hence, traditional drug susceptibility testing is still helpful for evaluation of such samples.